[Retracted] The Societal Consequences of the News Framing Regarding the Terrorist Attack in the Holy Artisan Café, Dhaka, Bangladesh on 1 July 2016 - Islam, Fatema (Asian Journal of Media and Communication, 2023)
This article analyzes the societal consequences of the news framing of the terrorist attack in the Holy Artisan Café of Bangladesh on 1st July 2016, which killed seventeen foreigners, three Bangladeshis, and two Bangladeshi police officers. Combining quantitative and qualitative research methods, this study investigated 134 news articles regarding the attack on the two prominent newspapers of Bangladesh: The Daily Star and The Prothom Alo, dated from 1 July 2016 to 1 July 2017. From a quantitative comparative framing analysis of these two newspapers, this study found that: 88.81% coverage were generically news articles, the major source (41.04%) of the news was Bangladesh Police, only 11.94% articles interpreted the reasons and political consequences of the terrorist attack, 88.16% news were descriptive, and the contextual framework of 63.43% news were episodic. The qualitative analysis found that the news coverage of the two newspapers regarding the attack had far-reaching societal consequences impacting public perceptions, government policies, security measures, and social dynamics.    [This article has been retracted by the editors due to redundant publication without proper attribution to previous sources or disclosure to the editor--based on COPE Standard]